Water-dependent charge-transfer-induced spin transition of Prussian blue analogues. Issue 42 (12th October 2016) - Ohmagari, Hitomi; Ohtani, Ryo; Nakaya, Manabu; Ohba, Masaaki; Nakamura, Masaaki; Lindoy, Leonard F.; Sato, Osamu; Hayami, Shinya
Abstract : Na0.46 Co[Fe(CN)6 ]0.78 (H2 O)1.31 shows a water-dependent charge-transfer-induced spin transition behavior caused by a change in coordination geometry at Co centers. Abstract : Cobalt–iron Prussian blue analogues are magnetic functional compounds that exhibit charge-transfer-induced spin transition (CTIST), however, the role of guest species such as water in influencing the magnetic behaviour has remained unclear. Here, we report the water-dependent CTIST behaviour of Na0.46 Co[Fe(CN)6 ]0.78 (H2 O)1.31 together with its single crystal X-ray structural analysis, for the first time.